Using XSLT to generate SQL a simple, adaptable example to get you started. - Watson, Greg
Examples of selecting data from a database to produce XML are not too difficult to find. A Google search or a visit to the XML section at your local bookstore will no doubt reveal several such examples. It can, however, be more difficult to locate examples of how to insert data from XML into a database. Even if you locate such examples, it can be a challenge (to say the least) to adapt them to large XML files in which the data you need resides in a selected number of elements nested several levels deep within the file.